2022
DOI: 10.1111/jonm.13814
|View full text |Cite
|
Sign up to set email alerts
|

A year after COVID‐19: Its impact on nurses' psychological well‐being

Abstract: Background Nurses' burnout and psychological well‐being are a significant concern during the pandemic. Aims The aim of this study is to (i) examine the level of burnout, anxiety, depression, perceived stress and self‐rated health for nurses at two time‐points, 2020 and 2021, and (ii) examine the socio‐demographic characteristics, work‐related factors and perceived workplace support factors in relation to the level of burnout. Methods This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…The results of our study contribute to a growing body of literature highlighting the significant impacts that the COVID-19 pandemic has had on the mental health of resident physicians 29 and other health care providers. 30 Future work is necessary to better describe the long-term effects of the pandemic on trainees and other members of the health care team.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study contribute to a growing body of literature highlighting the significant impacts that the COVID-19 pandemic has had on the mental health of resident physicians 29 and other health care providers. 30 Future work is necessary to better describe the long-term effects of the pandemic on trainees and other members of the health care team.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the peak of COVID-19. Research shows that 20 to 30 years old [8], female [8], single [9], childless [10], bachelor's degree [10], not appreciated by leaders [11], uneven workload [12], night shift nurses [13], fear of infection [14,15], worry about whether family members are infected [13] are all risk factors for job burnout of nurses during the COVID-19 pandemic. Nurses working at the peak of COVID-19 not only need to take into account the heavier work pressure than before, but also need to often face patients with poor medical effect, imminent end of life, and ethical and moral problems [16].…”
Section: Introductionmentioning
confidence: 99%
“…This situation caused them to work under intense stress (Alan et al, 2021 ; Murat et al, 2021 ). As a result, nurses working in pandemic wards and intensive care units experienced negative outcomes such as decreased job satisfaction and increased burnout and compassion fatigue (Aloweni et al, 2022 ; Xia et al, 2022 ). For better performance and patients' quality of care and safety is essential to minimize these negative outcomes and to improve the organizational well‐being of nurses (Della Bella et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have reported a high prevalence of compassion fatigue in nurses during the pandemic (Storm & Chen, 2021 ; Wang et al, 2022 ). Therefore, the COVID‐19 pandemic caused deleterious effects on frontline nurses' mental health (Aloweni et al, 2022 ; Murat et al, 2021 ). In this way, nurse managers' leadership behaviours become even more important in crises such as COVID‐19 that involve fear and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation